Thymus medulla under construction: Time and space oddities. Issue 4 (21st March 2016) - Alves, Nuno L.; Ribeiro, Ana R.
Abstract : The induction and maintenance of T‐cell tolerance depends on establishment of functionally competent medullary thymic epithelial cell microenvironments. In this issue, reports by Baik et al. and Mayer et al. decode novel developmentally related, but temporally distinct principles that underlie the homeostasis of the thymic medulla across life. Abstract : The development of effective T‐cell‐based immunotherapies to treat infection, cancer, and autoimmunity should incorporate the ground rules that control differentiation of T cells in the thymus. Within the thymus, thymic epithelial cells (TECs) provide microenvironments supportive of the generation and selection of T cells that are responsive to pathogen‐derived antigens, and yet tolerant to self‐determinants. Defects in TEC differentiation cause syndromes that range from immunodeficiency to autoimmunity, which makes the study of TECs of fundamental and clinical importance to comprehend how immunity and tolerance are balanced. Critical to tolerance induction are medullary thymic epithelial cells (mTECs), which purge autoreactive T cells, or redirect them to a regulatory T‐cell lineage. In this issue of the European Journal of Immunology, studies by Baik et al. and Mayer et al. [Eur. J. Immunol. 2016. 46: XXXX‐XXXX and 46: XXXX‐XXXX]) document novel spatial–temporal singularities in the lineage specification and maintenance of mTECs. While Baik et al. define a developmental checkpoint during mTEC specification in the embryo, Mayer et al. reveal that the generation and maintenance of the adult mTEC compartment is temporally controlled in vivo. The two reports described new developmentally related, but temporally distinct principles that underlie the homeostasis of the thymic medulla across life.